Current Use of Underage Alcohol Compliance Checks by Enforcement Agencies in the United States. (9th April 2014) - Erickson, Darin J.; Lenk, Kathleen M.; Sanem, Julia R.; Nelson, Toben F.; Jones‐Webb, Rhonda; Toomey, Traci L.
<x xml:space="preserve">Abstract</x> Background Compliance checks conducted by law enforcement agents can significantly reduce the likelihood of illegal alcohol sales to underage individuals, but these checks need to be conducted using optimal methods to maintain effectiveness. Methods We conducted a national survey of local and state enforcement agencies from 2010 to 2011 to assess: (i) how many agencies are currently conducting underage alcohol compliance checks, (ii) how many agencies that conduct compliance checks use optimal methods—including checking all establishments in the jurisdiction, conducting checks at least 3 to 4 times per year, conducting follow‐up checks within 3 months, and penalizing the licensee (not only the server/clerk) for failing a compliance check, and (iii) characteristics of the agencies that conduct compliance checks. Results Just over one‐third of local law enforcement agencies and over two‐thirds of state agencies reported conducting compliance checks. However, only a small percentage of the agencies (4 to 6%) reported using all of the optimal methods to maximize effectiveness of these compliance checks. Local law enforcement agencies with an alcohol‐related division, those with at least 1 full‐time officer assigned to work on alcohol, and those in larger communities were significantly more likely to conduct compliance checks. State agencies with more full‐time agents and those located in states where the state agency or both state and local enforcement agencies have primary responsibility (vs. only the local law agency) for enforcing alcohol retail laws were also more likely to conduct compliance checks; however, these agency characteristics did not remain statistically significant in the multivariate analyses. Conclusions Continued effort is needed to increase the number of local and state agencies conducting compliance checks using optimal methods to reduce youth access to alcohol.